Evaluation of diatomaceous earth in the removal of crystal violet dye in solution (2022)
In this research, the adsorption capacity of diatomaceous earth in the removal of the crystal violet dye (CV) in aqueous solution was evaluated. The experimental methodology began with the determination of the texture properties by adsorption-desorption isotherms with N2 a 77 K, the identification of functional groups by Fourier transform infrared spectrophotometry (FTIR), morphology by scanning electron microscopy (SEM) and, the pH of the isoelectric point by the point of zero charge (PZC). A categorical multifactorial design was developed with factors such as the initial concentration of the dye, the temperature and the initial pH of the solution. The maximum adsorption capacity was of 96.1 mg/g up 30ºC and pH 8, satisfactorily fitting the experimental data to the Langmuir isotherm model, suggesting a monolayer adsorption mechanism on a homogeneous surface. In conclusion, diatomaceous earth can be considered as an efficient adsorbent in the removal of CV in aqueous solution.